2021
DOI: 10.3389/fimmu.2021.696370
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Mediated Immunity to SARS-CoV-2 and Human Coronaviruses: Multiplex Beads Assay and Volumetric Absorptive Microsampling to Generate Immune Repertoire Cartography

Abstract: The COVID-19 pandemic is caused by SARS-CoV-2, a novel zoonotic coronavirus. Emerging evidence indicates that preexisting humoral immunity against other seasonal human coronaviruses (HCoVs) plays a critical role in the specific antibody response to SARS-CoV-2. However, current work to assess the effects of preexisting and cross-reactive anti-HCoVs antibodies has been limited. To address this issue, we have adapted our previously reported multiplex assay to simultaneously and quantitatively measure anti-HCoV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 39 publications
(70 reference statements)
5
22
0
Order By: Relevance
“…To date, antibody cross-reactivity has been inferred from indirect evidence in the form of boosted responses to endemic CoV [23][24][25][26][27] , and more conclusively observed for select monoclonal antibodies that have been cloned and cross tested 33,34 . To better generalize the more definitive monoclonal studies, we sought to directly define the cross-reactivity of polyclonal antibodies raised following SARS-CoV-2 infection.…”
Section: Direct Evidence Of Molecular Cross-reactivity Of Sars-cov-2 and Oc43-specific Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, antibody cross-reactivity has been inferred from indirect evidence in the form of boosted responses to endemic CoV [23][24][25][26][27] , and more conclusively observed for select monoclonal antibodies that have been cloned and cross tested 33,34 . To better generalize the more definitive monoclonal studies, we sought to directly define the cross-reactivity of polyclonal antibodies raised following SARS-CoV-2 infection.…”
Section: Direct Evidence Of Molecular Cross-reactivity Of Sars-cov-2 and Oc43-specific Antibodiesmentioning
confidence: 99%
“…Numerous studies have observed elevated responses to endemic CoV following SARS-CoV-2 infection [23][24][25][26][27] , and more recent work has shown that the magnitude of this "back-boosting" effect is inversely correlated with the induction of IgG and IgM against to SARS-CoV-2 spike (S) protein 28 . Given differential degrees of homology between the receptor binding domain (RBD) in S1 that is the target of the majority of neutralizing antibodies, and the better conserved S2 domain that may be the target of antibodies with diverse effector functions but which are rarely neutralizing, the original antigenic sin hypothesis suggests that lower titers of neutralizing antibodies against SARS-CoV-2 may result from boosting of pre-existing cross-reactive lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, T cell-mediated anti-SARS-CoV-2 responses were found in unexposed human, indicating a cross-reaction between human CoVs and SARS-CoV-2 (10)(11)(12)(13)(14). Accumulating evidence suggests that pre-existing humoral immunity to sCoVs may play a role in the specific anti-SARS-CoV-2 antibody responses (15), but this possibility is controversial (16,17). Some studies showed that elevated levels of pre-existing antibodies against sCoVs, specifically OC43 and HKU1, were associated with a less severe course of COVID-19, suggesting a protective effect of prior exposure to sCoVs (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Levels of binding IgG Abs from serum, MPAbs, and PPAbs were measured against a broad range of coronavirus proteins (Table S2) by multiplex assay, as recently described [54]. Sera was diluted to 1:1000 and Abs secreted by PBs and post-stimulated MBCs were diluted to 1:2, all with PBS.…”
Section: Coronavirus Multiplex Assaymentioning
confidence: 99%